Calibração multivariada para sistemas com bandas sobrepostas através da análise da fatores do tipo Q Q mode factor multivariate calibration for systems with overlapped bands - Ieda Spacino Scarminio; Dilson Norio Ishikawa; Wagner José Barreto; Édio Luiz Paczkowski; Iara Cintra Arruda (Química Nova, 1998)
A multivariate calibration method to determine chemical compositions of systems with severely overlapped bands is proposed. Q mode factors are determined from the spectral data and subsequently rotated using the varimax and oblique transformation of Imbrie. The method is applied to two sets of simulated data to test the sensitivity of analytical results to random experimental error. The chemical concentrations of alanine and threonine mixture are determined from spectral data of the 302,5 - 548,5 nm region.